2003
DOI: 10.2108/zsj.20.533
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Tachykinin-Related Peptides, Their Receptors, and Invertebrate Tachykinins: A review

Abstract: Tachykinins (TKs) constitute the largest vertebrate neuropeptide family with multifunctions in central and peripheral tissues. In several invertebrate species, two types of structurally related peptides, 'tachykinin-related peptides (TKRPs)' and 'invertebrate tachykinins (inv-TKs)' have been identified. TKRPs, isolated from the nerve and/or gut tissues, contain the common C-terminal sequence -Phe-X-Gly-Y-Arg-NH(2) (X and Y are variable) analogous to the vertebrate TK consensus -Phe-X-Gly-Leu-Met-NH(2), and exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 81 publications
2
65
0
2
Order By: Relevance
“…However, only two peptides, GnRH and cionin (CCK/gastrin-related peptide), have so far been identified from ascidians (43)(44)(45), although the presence of TK-like compounds in ascidians was implied by previous immunohistochemical analyses and radioimmunoassays for several ascidian tissues (24 -28). Furthermore, TKRPs, but not TKs, have been found in invertebrates, which complicates the evolutionary aspect of the TK family (7,20). In this study, we showed the structure, activity, and localization of a TK peptide, Ci-TK, and its receptor, Ci-TK-R, of an ascidian, C. intestinalis.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…However, only two peptides, GnRH and cionin (CCK/gastrin-related peptide), have so far been identified from ascidians (43)(44)(45), although the presence of TK-like compounds in ascidians was implied by previous immunohistochemical analyses and radioimmunoassays for several ascidian tissues (24 -28). Furthermore, TKRPs, but not TKs, have been found in invertebrates, which complicates the evolutionary aspect of the TK family (7,20). In this study, we showed the structure, activity, and localization of a TK peptide, Ci-TK, and its receptor, Ci-TK-R, of an ascidian, C. intestinalis.…”
Section: Discussionmentioning
confidence: 81%
“…Contractile Activities of Ci-TKs on Gut Tissues-TKs are known to induce a characteristic contraction of gut tissues (1,7,19,20). Nevertheless, Ci-TKs had no contractile effect on the Ciona gut (data not shown), most likely due to the absence of intestinal muscular tissues in the ascidian gut (29).…”
Section: Identification Of the Ci-tk Peptides Cdna And Genomicmentioning
confidence: 91%
See 2 more Smart Citations
“…In protostomes, TK-related peptides (TKRPs) exert a TK-like contractile activity and the expression of the tkrp gene is observed in the central nervous system (Satake et al, 2003;Satake & Kawada, 2006a). However, they contain the analogous Phe-Xaa1-(Gly/Ala)-Xaa2-Arg-NH 2 consensus (Table 1), and TKRP precursors encode multiple TKRP sequences (Satake et al, 2003;Satake and Kawada, 2006a), which are totally distinct from those of vertebrate TKs. These findings suggest that tkrp genes and tk genes diverged in distinct evolutionary lineages.…”
Section: Tks In C Intestinalismentioning
confidence: 99%